Financial Feasibility of Small Scale Liquefied Natural Gas Carrier (SSLNGC) Investment: A Capital Budgeting Analysis For PT Bahtera Adhiguna Putera (BAg) - Namira Jayarachman, Marsha; Yudha Sudrajad, Oktofa (International Journal of Science, Technology & Management, 2026)
Indonesia’s target to achieve net zero emissions by 2060 requires a strategic shift from coal to cleaner energy sources, with Liquefied Natural Gas (LNG) serving as a key transitional fuel. PT Bahtera Adhiguna Putera (BAg), a subsidiary of PT PLN Energi Primer Indonesia (PLN EPI), plays a vital role in energy logistics but currently lacks the fleet capacity to transport LNG. To address this gap, this study evaluates the financial feasibility of investing a Small Scale Liquefied Natural Gas Carriers (SSLNGC) through a capital budgeting approach. The research uses both qualitative and quantitative methods. PESTEL analysis is applied to assess the external environment and operational readiness, while capital budgeting tools such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Weighted Average Cost of Capital (WACC) are used to evaluate financial performance. The study tests several financing structure which is using 100% internal cash for Scenario 1 and mixed financing for Scenario 2 which ratio is 20% internal cash and 80% SHL scenario. A sensitivity analysis is also conducted to identify the most critical variables affecting investment outcomes and to measure the project’s financial resilience under different market conditions. The results show that the SSLNGC investment is both technically and financially feasible. The vessel’s capacity is suitable for port depth limitations and LNG demand in the targeted region. Financially, the investment is feasible, and the most optimal financing structure is Scenario 2 because has smaller WACC, higher NPV values, higher IRR compared to the WACC, and a reasonable payback period, confirming the project’s profitability. This also supported by the smaller value in the Scenario 2 sensitivity analysis calculation compared to Scenario 1. To keep the project profitable in the long term, BAg needs to ensure all the financial and operational key variables remain the same as the overall feasibility calculation is highly dependent on those variables.